THEORETICAL ASPECTS OF RESEARCH OF EMPLOYMENT PROBLEMS OF PERSONS WITH DISABILITIES - BOIKIVSKA, GALYNA; HLADUN, SVITLANA; KUTNIA, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the problems of employment of persons with disabilities and the peculiarities of regulatory and legal support in the field of regulation of employment of persons with disabilities. The employment rate of people with disabilities is a priority for a good life and an important indicator that gives them the right to feel like full members of society and get a positive impact on their psychological state. The concepts of state policy in the field of employment regulation of persons with disabilities are analyzed. The accumulated international and domestic experience shows that the effective solution of these problems is possible only within the model in which the political goals of the state, legal, economic, organizational and scientific skills, components of the social protection of persons with disabilities are pensions, state social insurance, state social insurance. support, system of benefits and compensations. Ukraine only at the first stage to inclusive development Inclusive development is based on the distribution of welfare, elimination of discrimination and participation of all labor resources, which provides a high standard of living for the majority of the population. Approaches to the definition of the terms "disability" and "persons with disabilities" in the legislation of different countries are systematized. Domestic legislation provides for a number of economic levers of influence on enterprises, institutions, organizations that use hired labor, in order to ensure employment of this category of citizens. The main problems of employment of people with disabilities and ways to overcome them are identified. Integrating people with disabilities into the labor market is a complex multilateral process that requires each country to find a specific combination of measures and funding opportunities. Successful implementation of measures is essential to create a comprehensive labor market with equal opportunities for all members of society.